Reading Development from Kindergarten to Age 18: The Role of Gender and Parental Education - Manu Mari; Torppa Minna; Vasalampi Kati; Lerkkanen Marja-Kristiina; Poikkeus Anna-Maija; Niemi Pekka (WILEY, 2025)
The gender difference in reading achievement in favor of adolescent girls is a robust finding in the literature, but the evidence is mixed when considering younger children. The present study followed the development of reading skills among Finnish children (N = 1867) from kindergarten age (6 years) to 18 years of age to determine the onset of gender differences and to identify the subskills which present gender differences. Additionally, associations between parents' educational levels and children's reading development from kindergarten to the end of comprehensive school were examined to determine whether the effect of parental education varied by child's gender. The results showed that girls outperformed boys in almost all prereading and reading skills from kindergarten age onwards. The gender difference in reading fluency increased steadily across the school years (Cohen's d = .26–.59) and remained evident also among 18-year-olds (d = .42). In terms of reading comprehension, the gender difference was small but increased with age (d = .17–.36). Parents' education levels were associated with children's reading development and children of higher educated parents manifested the best performance. Interaction effects were found between child's gender and their fathers' education levels: lower education levels were associated with poorer PISA reading performance among boys, but not among girls. The results suggest that gender differences in reading performance have an early onset, they increase throughout the school years, and boys of fathers with low education are particularly at risk of falling behind in their development of reading comprehension skill.